(untitled) (London Journal of Engineering Research, 2024)
This article explored that the limestone and iron ore becomes into raw materials for energy production by rely on carbon gasification reaction (C+CO2=2CO) . Converting a lime calcining kiln into an electric gas producer is the most economical-effective emission reduction? achieve 0capture cost. The total CO2 discharged from the two industries of cement and steel is 3.664 billion tons, which can produce 3,729.952 billion m3CO, equivalent to 1,376.4 billion m3 of natural gas energy, equivalent to the energy transported by 25 Nord Stream 2 lines annually. Unfortunately, it is currently wasted? The water-gas instead of the direct combustion of coal should be a feasible technical route, An expensive CCS technology route can be promoted, and a profitable water-gas technology route should be more welcome.